2023
DOI: 10.1088/1741-4326/acc344
|View full text |Cite
|
Sign up to set email alerts
|

Gyrokinetic simulations of electrostatic microturbulence in ADITYA-U tokamak

Abstract: Global gyrokinetic simulations of the electrostatic microturbulence driven by the pressure gradients of thermal ions and electrons are carried out for the ADITYA-U tokamak geometry using its experimental plasma profiles and with collisional effects. The dominant instability is trapped electron mode (TEM) based on the linear eigenmode structure and its propagation in the electron diamagnetic direction. Collisional effects suppress turbulence and transport to a certain extent. Zonal flow is not playing a critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 62 publications
3
8
0
Order By: Relevance
“…In the outermost region, a large drive (profile gradient) excites the TEM instability which is consistent with the earlier gyrokinetic simulations of microturbulence in ADITYA-U using GTC [37]. It is worth mentioning that the TEM discussed in this work is collisionless trapped electron mode (CTEM), though the previously performed gyrokinetic simulations of TEM in ADITYA-U show that the collision can reduce turbulence and associated transport to a certain extent [37]. However, the collisions can have a destabilizing effect on the dissipative trapped electron mode (DTEM) [53] as has been found in the pedestal of HL-2A [54] and EAST [55].…”
Section: Microturbulence Simulationssupporting
confidence: 90%
See 1 more Smart Citation
“…In the outermost region, a large drive (profile gradient) excites the TEM instability which is consistent with the earlier gyrokinetic simulations of microturbulence in ADITYA-U using GTC [37]. It is worth mentioning that the TEM discussed in this work is collisionless trapped electron mode (CTEM), though the previously performed gyrokinetic simulations of TEM in ADITYA-U show that the collision can reduce turbulence and associated transport to a certain extent [37]. However, the collisions can have a destabilizing effect on the dissipative trapped electron mode (DTEM) [53] as has been found in the pedestal of HL-2A [54] and EAST [55].…”
Section: Microturbulence Simulationssupporting
confidence: 90%
“…The electron temperature is ∼450 eV and 500 eV, before and after argon gas seeding, respectively. The onaxis ion temperature is assumed to be one-third of the electron temperature [37], and near the edge, electron and ion temperatures are considered the same. The form of the ion temperature profile is assumed to be the same as that of the electron temperature profile.…”
Section: Gas Seeding Experiments In Aditya-umentioning
confidence: 99%
“…The discharges used in present study are in LOC regime, from the linear relation between plasma density and energy confinement time [45]. Also, the Gyro-kinetic simulation studies in similar LOC discharges [46] shows that TEM are most dominant modes in our machine [47]. In LOC regime, there is a possibility of existence of TEM turbulence and can contribute to electron heat diffusivity, given the electron temperature gradient in discharges is above the critical threshold [46].…”
Section: Discussionmentioning
confidence: 75%
“…A fluidkinetic hybrid model [57] has been implemented in GTC to overcome these limitations. This model has been used earlier to simulate the micro-instabilities in LHD [36], W7-X [58] stellarators, and tokamak [24]. In this model, the electron distribution function is written as a sum of adiabatic and nonadiabatic parts, fe = f 0 e eϕ/Te + δge.…”
Section: Model Equationsmentioning
confidence: 99%
“…Advancements in high-performance computing have made it possible to validate the gyrokinetic model. Several attempts in this direction have shown that gyrokinetics accurately describes turbulence and transport in fusion plasmas [22][23][24][25][26]. However, the gyrokinetic simulations of microturbulence using realistic device geometries and experimental profiles face severe numerical challenges.…”
Section: Introductionmentioning
confidence: 99%